Penyuluhan Kesehatan tentang Anemia pada Ibu Hamil di Desa Talabiu Kabupaten Bima - Nur Fitriyah; Erlina Fauzia; Nurfadila Nurfadila; Sakratul Jannah; Istiqomah istiqomah (Idea Pengabdian Masyarakat, 2022)
Anemia is a condition in which the body has too few red blood cells, where the red blood cells contain hemoglobin which functions as a carrier of oxygen to all body tissues. Pregnant women are susceptible to anemia because during pregnancy the body undergoes very significant changes, one of which is the high need for oxygen to share with the fetus in the womb and the need for nutrients increases and changes occur in the blood and bone marrow. In handling anemia, the Ministry of Health has a policy so that anemia does not have an impact on conditions of childbirth and postpartum which are at risk of death. The high prevalence of anemia can lead to negative impacts such as disruption and inhibition of growth and lack of hemoglobin in the blood which results in a lack of oxygen being transferred throughout the body and brain. This service is carried out at the Talabiu village office. This activity aims to increase participants' knowledge about anemia in pregnancy and add insight that anemia in pregnancy is a condition that can trigger complications, one of which is the cause of bleeding. This service method is through lectures/counseling, discussion and question and answer with the presentation of material in the form of powerpoint. As a result of our dedication, we got enthusiastic participants who were active in asking questions. Participants said their knowledge increased about anemia in pregnancy.